2008
DOI: 10.1088/0022-3727/41/5/055406
|View full text |Cite
|
Sign up to set email alerts
|

High-rate, low-temperature synthesis of composition controlled hydrogenated amorphous silicon carbide films in low-frequency inductively coupled plasmas

Abstract: It is commonly believed that in order to synthesize high-quality hydrogenated amorphous silicon carbide (a-Si1−xCx : H) films at competitive deposition rates it is necessary to operate plasma discharges at high power regimes and with heavy hydrogen dilution. Here we report on the fabrication of hydrogenated amorphous silicon carbide films with different carbon contents x (ranging from 0.09 to 0.71) at high deposition rates using inductively coupled plasma (ICP) chemical vapour deposition with no hydrogen dilut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 65 publications
3
44
0
Order By: Relevance
“…At a glimpse, one can also notice that, with the increase of the carbon content X C , the intensity of the Si-H wagging or rocking band gradually diminishes while the intensities of the Si-H and Si-C stretching bands reveal the opposite trend. This observation agrees well with our previous work on the growth of hydrogenated amorphous silicon carbide films [24]. In this previous work, it was clearly demonstrated that the magnitude of the Si-H wagging or rocking absorption peak gradually decreased and eventually disappeared completely at an intermediate carbon content X C of 50at.% while the magnitudes of the Si-H and Si-C stretching absorption peaks had a maximum value at an intermediate carbon content X C of 50at.% [24].…”
Section: Ftir Absorption Spectrasupporting
confidence: 94%
See 3 more Smart Citations
“…At a glimpse, one can also notice that, with the increase of the carbon content X C , the intensity of the Si-H wagging or rocking band gradually diminishes while the intensities of the Si-H and Si-C stretching bands reveal the opposite trend. This observation agrees well with our previous work on the growth of hydrogenated amorphous silicon carbide films [24]. In this previous work, it was clearly demonstrated that the magnitude of the Si-H wagging or rocking absorption peak gradually decreased and eventually disappeared completely at an intermediate carbon content X C of 50at.% while the magnitudes of the Si-H and Si-C stretching absorption peaks had a maximum value at an intermediate carbon content X C of 50at.% [24].…”
Section: Ftir Absorption Spectrasupporting
confidence: 94%
“…The appearance of these strong interference fringes suggests that the surface of the deposited films is quite smooth. However, the absorption peaks attributed to the characteristic Si-H wagging or rocking mode located at $640 cm À1 , the stretching mode of Si-C bonds located at $780 cm À1 , and the Si-H stretching mode located at $2100 cm À1 , respectively, can still be distinctly detected in the spectra [24,28]. At a glimpse, one can also notice that, with the increase of the carbon content X C , the intensity of the Si-H wagging or rocking band gradually diminishes while the intensities of the Si-H and Si-C stretching bands reveal the opposite trend.…”
Section: Ftir Absorption Spectramentioning
confidence: 94%
See 2 more Smart Citations
“…Gaseous plasmas represent an ideal fabrication environment for this purpose. A high degree of compositional control during nanoassembly has been demonstrated for plasma-based processes both computationally [113,116,134,135] and experimentally [136][137][138][139][140][141].…”
Section: Tailoring Metal Nanoarraysmentioning
confidence: 99%